Crohn's disease: small bowel motility impairment correlates with inflammatory‐related markers C‐reactive protein and calprotectin. Issue 6 (18th March 2013) - Bickelhaupt, S.; Pazahr, S.; Chuck, N.; Blume, I.; Froehlich, J. M.; Cattin, R.; Raible, S.; Bouquet, H.; Bill, U.; Rogler, G.; Frei, P.; Boss, A.; et al.
Abstract Background To evaluate the correlation between the levels of C‐reactive protein (CRP), calprotectin, and small bowel motility in patients with Crohn's disease assessed with MRI. Methods This prospective institutional review board approved study included magnetic resonance imaging enterography (MRE) and analyses of inflammatory markers in blood (C‐reactive protein) and feces (calprotectin). For cine MRE, a coronal 2D‐T2w sequence was used on a 1.5 T MRI system. Small bowel motility was analyzed in 13 patients using dedicated magnetic resonance MR‐motility assessment software (Motasso). Contraction frequency, amplitude, amplitude diameter ratio, and luminal diameter were determined as well as the blood levels of CRP (mg L−1) and fecal levels of calprotectin (ug g−1). Statistics were calculated using Pearson's correlation coefficient. Key Results A significant inverse linear correlation was found between the contraction frequency and both the level of CRP (r = −0.701, P = 0.008) and calprotectin (r = −0.805, P = 0.001). Dilatation of small bowel diameter significantly correlated with calprotectin levels (r = 0.857, P =< 0.001) but not with CRP (r = 0.447, P = 0.126). The absolute amplitude of the contractions did not correlate neither with the level of CRP (r = −0.527, P = 0.064) nor with calprotectin (r = −0.612, P = 0.026). The ratio describing the contraction amplitude relatively to the individual luminal diameter significantly correlated with calprotectin (r = 0.736, P = 0.004) and with CRP (r = 0.577, P = 0.039). Conclusions & Inferences Alterations of small bowel motility during CD flares significantly correlate with the level of calprotectin and CRP indicating that they represent inflammatory activity.